Assessment Of Groundwater Quality For Drinking By Water Quality Index (WQI) In Sabratha City, Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
Consumers are reacting with water quality problems by using household wells, which is the only water source available in this city. Therefore, this study was conducted in Sabratha city with the major objective of assess suitability of groundwater quality for drinking purposes through water quality index (WQI) investigations. Water samples were collected from (48 wells) in different locations of the city by using GPS to locate the coordinates of wells in May 2016. For calculating WQI, eleven parameters have considered such as: EC, pH , TDS , 〖Cl〗^-, 〖HCO〗_3^- , 〖SO〗_4^(-2) , 〖NO〗_3^- , 〖Ca〗^(+2) , 〖Mg〗^(+2), 〖Na〗^(+  ) , K^+. The suitability of groundwater in the study area for human consumption purpose is achieved by WQI according to the guideline values of Libyan Standard Specifications (2011). The results showed that the water quality index for wells samples were varying from unsuitable to good, only seven wells, the water quality coefficient values were good for drinking.
Keywords: Groundwater; Water Quality Index (QWI); Libyan Standard Specifications; Sabratha-Libya